Aberrant expression of SNHG12 contributes to N, N-dimethylformamide-induced hepatic apoptosis both in short-term and long-term DMF exposure. Issue 5 (27th August 2021) - Liu, Ye; Wen, Cuiju; Zhang, Yangchun; Liu, Ziqi; He, Qianmei; Cui, Mengxing; Peng, Honghao; Wang, Yuqing; Zhang, Xueying; Li, Xudong; Wang, Qing
Abstract: N, N -Dimethylformamide (DMF) can cause liver damage in occupationally exposed workers, but the molecular mechanism of DMF-induced liver damage has not been fully elucidated. Researches have proved that lncRNA plays a major function in chemical-induced liver toxicity and can be used as a biomarker and therapeutic target for liver injury. In order to verify that lncRNA also participates in DMF-induced liver damage, we treated HL-7702 cells with 75 or 150 mM DMF, and obtained lncRNA expression profiles through high-throughput sequencing. Among the differentially expressed lncRNAs, lncRNA SNHG12 was proved to be significantly downregulated in DMF-treated HL-7702 cells and participate in DMF-mediated apoptosis, even under long-term low-dose DMF exposure (5–10 mM, 8 weeks). In addition, according to bioinformatics analysis, miR-218-5p is expected to be a potential target of SNHG12, which was verified by the dual luciferase reporter assay in HEK293FT cells. MiR-218-5p mimic can induce apoptosis in HL-7702 cells. Among the predicted targets of miR-218-5p, protein kinase C epsilon (PRKCE) was reported to be involved in apoptosis, and was indeed downregulated by miR-218-5p mimic in our study. Further experiments showed that changes of the expression of SNHG12 can affect the expression of PRKCE. In the epidemiological study of occupational population, we also found that SNHG12 was downregulated in the serum exosomes of workers exposed to DMF. These results indicated that SNHG12 can mediate DMF-induced apoptosis of HL-7702 cells through miR-218-5p/PRKCE pathway. Graphical Abstract: Graphical abstract. LncRNA SNHG12 regulates DMF-induced hepatic apoptosis through has-miR-218-5p/PRKCE axis. Used Pathway Builder Tool 2.0 software (Protein Lounge Inc.) to draw the graph. DMF, N, N -dimethylformamide